THE EFFECT OF GENERAL ALLOCATION FUNDS AND FUEL SUBSIDIES ON CAPITAL EXPENDITURES IN INDONESIA - Yuanda Shinta Qwanthala; Ratna Husen; Murtala Murtala (LPPM Universitas Malikussaleh, 2022)
The purpose of this study is to examine the impact of general allocation funds and fuel subsidies on capital expenditures in Indonesia. From 1990 through 2020, this analysis makes use of secondary data from the Indonesian Ministry of Finance and the World Bank. The data was examined using the eviews 10 analytic tool and the multiple linear regression approach. According to the findings of the study, the general allocation fund has a favorable and considerable impact on capital spending in Indonesia. Meanwhile, fuel subsidies have a considerable negative impact on capital expenditures in Indonesia. The size of the effect of general allocation funds and fuel subsidies on capital expenditures is 95,66%, whereas the influence of other general allocation funds outside of this model is 4,34%. It is advised that government subsidies be used as efficiently as possible in order to promote wellbeing.